2010
DOI: 10.1123/pes.22.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Adiposity and Health-Related Physical Fitness Test Performances From Early Childhood Through Elementary School

Abstract: This study tracked health-related physical fitness measurements in children, including sum of triceps and medial calf skinfolds, timed 1-mile run/walk, 1-min bent-knee sit-up, pull-up, and sit-and-reach values. Results are from 409 boys and 409 girls tested in kindergarten and fifth grade, also retaining their first, second, third, and fourth grade data. In separate gender analyses, Spearman's rho correlations were significant (p < .001) for all grade level pair combinations for each variable. Five-yr tracking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 0 publications
4
20
0
1
Order By: Relevance
“…BMI and flexibility are probably quite stable in childhood and adolescence [15]. Falk et al [10], McMillan and Erdmann [25], and Vandorpe et al [26] tracked quite similar test groups and also used field-tests in their studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…BMI and flexibility are probably quite stable in childhood and adolescence [15]. Falk et al [10], McMillan and Erdmann [25], and Vandorpe et al [26] tracked quite similar test groups and also used field-tests in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…McMillan and Erdmann [25] applied sit-ups and a sit and reach test to check strength and flexibility. Over three years of tracking (Kindergarten-Grade 2; 6.1 ± 0.3 years), they found correlations in sit-ups of r = .44 (m.) and r = .39 (f.) and in sit and reach r = .48 (m.) and .52 (f.).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As muscular fitness tracks from childhood into adulthood (McMillan & Erdmann, 2010, Marshall et al, 1998 it is important to identify factors associated with its development in youth. Muscular fitness is related to adiposity (Deforche et al, 2003 and habitual physical activity (Moliner-Urdiales et al, 2010a) but these relationship are less widely reported than are the predictors of cardiorespiratory fitness.…”
Section: Introductionmentioning
confidence: 99%